2000
DOI: 10.1046/j.1365-2419.2000.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic approaches to remote species identification: a review

Abstract: Noninvasive species identification remains a long‐term goal of fishers, researchers, and resource managers who use sound to locate, map, and count aquatic organisms. Since the first biological applications of underwater acoustics, four approaches have been used singly or in combination to survey marine and freshwater environments: passive sonar; prior knowledge and direct sampling; echo statistics from high‐frequency measures; and matching models to low‐frequency measures. Echo amplitudes or targets measured u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
137
0
11

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(149 citation statements)
references
References 154 publications
(172 reference statements)
1
137
0
11
Order By: Relevance
“…Active acoustics is well established in fishery biology as a method using high-frequency echosounders (.10 kHz) to estimate abundance of the fishes and their habitat (MacLennan and Simmons 1992). One area that is still problematic for active acoustic approaches is remote species identification (Horne 2000); a solution is passive acoustic approaches, which can be used to identify species . Passive acoustics also has a long history in fish biology (Tower 1908;Burkenroad 1931;Fish and Mowbray 1970;Mok and Gilmore 1983;Luczkovich et al 1999Luczkovich et al , 2000 but is not widely used by fishery biologists.…”
mentioning
confidence: 99%
“…Active acoustics is well established in fishery biology as a method using high-frequency echosounders (.10 kHz) to estimate abundance of the fishes and their habitat (MacLennan and Simmons 1992). One area that is still problematic for active acoustic approaches is remote species identification (Horne 2000); a solution is passive acoustic approaches, which can be used to identify species . Passive acoustics also has a long history in fish biology (Tower 1908;Burkenroad 1931;Fish and Mowbray 1970;Mok and Gilmore 1983;Luczkovich et al 1999Luczkovich et al , 2000 but is not widely used by fishery biologists.…”
mentioning
confidence: 99%
“…Algunos autores han utilizado diferentes técnicas con resultados favorables para la identificación automática de cardúmenes monoespecíficos (Horne, 2000;Fernandes et al, 2006), utilizando información de tamaño, localización y eco-intensidad de los cardúmenes de peces. Sin embargo, el problema persiste cuando se presentan cardúmenes multiespecíficos (Fernandes, 2009).…”
Section: Introductionunclassified
“…As inheritance of hydro acoustic, fisheries acoustic has also two major divisions: active and passive one. Refer to Horne (2000) active acoustic includes subjects such as echo sounder and sonar, where pulses of sound are transmitted into the water and reflect off objects such as fish, submarines, or seabed.…”
Section: Introductionmentioning
confidence: 99%
“…Horne (2003) also identified that the ratio of acoustic wavelength to fish length had influence to acoustic backscattering. Moreover, Horne (2000) divide the factors affecting acoustic backscattering into physical factors such associated with the transmission of sound through a compressible fluid, and the biological factors associated with the location, reflective properties, and behavior of the target. Furthermore, Foote (1990a) and Ona (1990) defined that the biological factors composed of behavioral, morphological, ontogenetic, and physiological factors.…”
Section: Introductionmentioning
confidence: 99%